Representasi Citra Ibu Dalam Lirik Lagu Bertaut Karya Nadin Amizah (E-Jurnal Medium, 2022)
Representation is a sign or form of meaning contained in a message. Music is a medium that can be used to give messages to many people. Through music, a wide audience or the general public can be influenced by the messages the music creator wants to convey. Like the message about the image of a mother contained in the song Linked by Nadin Amizah, the song describes the image of a mother. The purpose of this study was to determine the representation of the image of a mother listed in the song Bertaut. This study uses a qualitative approach and uses the theory of Ferdinand De Saussure. The results obtained after doing this research are Bertaut by Nadin Amizah describes various forms of images of a mother such as the love of a mother given to her child. Keywords: Mother's image, Nadin Amizah, Bertaut Song Lyrics, Representation